1997
DOI: 10.1002/pro.5560061121
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary crystal structure determination of the alkaline protease from the Antarctic psychrophile pseudomonas aeruginosa

Abstract: Abstract:A cold alkaline protease, isolated from an Antarctic Pseudomonas aeruginosa strain, has been purified and crystallized. Large crystals were obtained in the presence of PEG 6000 at pH 7 and pH 8. They belong to the space group P2,2,2,. A complete data set to 2.1 A resolution has been measured. The structure has been determined by the molecular replacement method using the coordinates of the mesophilic alkaline protease as a model. The molecular replacement solution displays a correlation coefficient of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Many investigators have compared sequence and structure-based parameters among thermophilic and mesophilic proteins [ 10 ]. With the advent of pioneering efforts in late 1990's in solving three dimensional structures of cryophilic enzymes such as alpha-amylase [ 11 ]; alkaline protease [ 12 ]; triose phosphate isomerase [ 13 ]; malate dehydrogenase [ 14 ] from Antarctic microorganisms, and due to handful of available structures in the protein data bank (PDB), groups have focused to address the structural basis of proteins in cold adaptation [ 4 , 15 - 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have compared sequence and structure-based parameters among thermophilic and mesophilic proteins [ 10 ]. With the advent of pioneering efforts in late 1990's in solving three dimensional structures of cryophilic enzymes such as alpha-amylase [ 11 ]; alkaline protease [ 12 ]; triose phosphate isomerase [ 13 ]; malate dehydrogenase [ 14 ] from Antarctic microorganisms, and due to handful of available structures in the protein data bank (PDB), groups have focused to address the structural basis of proteins in cold adaptation [ 4 , 15 - 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 3D structural comparisons between mesophilic and psychrophilic cellulases are required in order to understand how proteins can adapt to low temperatures. The first report on the structure of a psychrophilic protein, a cold-active α-amylase from the antarctic psychrophile Alteromonas haloplanctis A23, came in the year 1996 [2], which was followed by a preliminary crystal structure determination of the alkaline protease from the antarctic psychrophile Pseudomonas aeruginosa [42]. However, the 3D structure of psychrophilic cellulases was not known till 2003, when a first paper appeared on the crystallization and preliminary X-ray crystallographic studies of a psychrophilic cellulase from Pseudoalteromonas haloplanktis [44].…”
Section: Insight Into the Crystal Structure Of Cold-adapted Cellulasesmentioning
confidence: 99%
“…Moreover use of cellulase can reduce the processing cost. Nilsson reported that cellulase enzymes are used to weaken the cellulose polymer and helps in dislodging the weakened fiber by mechanical process well known as "Biopolishing" [47].…”
Section: Enzymes From Marine Cold Loving Microorganismsmentioning
confidence: 99%